2016
DOI: 10.1111/jace.14450
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Density Open Cellular Silicon Carbide Foams from Sucrose and Silicon Powder

Abstract: Open cellular SiC foams with low densities were prepared by thermo‐foaming and setting (130°C–150°C) of silicon powder dispersions in molten sucrose followed by pyrolysis and reaction sintering at 1500°C. The bubbles generated in the dispersion by water vapor produced by the –OH condensation was stabilized by the adsorption of silicon particles on the air‐molten sucrose interface. The composition of a sucrose‐silicon powder mixture for producing SiC foam without considerable unreacted carbon was optimized. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…3a. Benchmarked against the light weight existing foams with density values of ρ = 0.391 ~ 0.514 g/cm 3 , we found that our foams possess higher compression strengths when compared to the values reported in the literatures (Table 1) [30][31][32][33]. The composition of slurry is an important factor affecting the mechanical properties of silicon carbide foams.…”
Section: Mechanical Propertiessupporting
confidence: 52%
“…3a. Benchmarked against the light weight existing foams with density values of ρ = 0.391 ~ 0.514 g/cm 3 , we found that our foams possess higher compression strengths when compared to the values reported in the literatures (Table 1) [30][31][32][33]. The composition of slurry is an important factor affecting the mechanical properties of silicon carbide foams.…”
Section: Mechanical Propertiessupporting
confidence: 52%
“…The XRD spectrum of the sample heat‐treated at 1600°C shows no peak corresponding to silicon. On the other hand, all well‐defined peaks corresponding to β‐SiC are observed . This indicates the complete conversion of silicon present in the body to SiC.…”
Section: Resultsmentioning
confidence: 93%
“…The in situ growth of SiC nanowires on the cell wall surfaces is observed during the pyrolysis and subsequent high‐temperature heat treatment of preceramic polymer foams . The formation of SiC nanowires is also reported during the reaction between silicon and carbon in silicon‐carbon composite foam to form SiC foam . Alternatively, SiC nanowires are incorporated on the cell walls of SiC foams by a chemical infiltration method .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations